Analisis Framing dalam Pemberitaan Quick Count Pilpres 2019 pada Makassar.Tribunnews.com - Rita Sugiarti; Muhammad Yahya (Journal of Communication Sciences (JCoS), 2020)
The media, especially online media, highlighted the quick count of the 2019 presidential election. Makassar.tribunnews.com is one of the online media that contains a lot of news related to the 2019 Presidential Election quick count, news on the quick count was intensively carried out by Makassar.tribunnews.com when the presidential election was approaching until the presidential election was completed in Indonesia. In its reporting, Makassar.tribunnews.com describes many things about the quick count, including the results of the quick count conducted by the survey institute, and the responses of the two presidential candidates regarding the results of the quick count. This study aims to find out how Makassar.tribunnews.com frames the 2019 Presidential Election quick count reporting using the Robert N Entman framing analysis model. The results of this study Makassar.tribunnews.com are more informative and try to lead public opinion by showing differences in the results of surveys conducted by PT. LSI Denny JA and BPN Prabowo-Sandi.